Nonparametric identification of production function, total factor productivity, and markup from revenue data - Kasahara, Hiroyuki,Sugita, Yoichi (CESifo, Center for Economic Studies & Ifo Institute, 2020)
Commonly used methods of production function estimation assume that a firm's output quantity can be observed as data, but typical datasets contain only revenue, not output quantity. We examine the nonparametric identification of production function from revenue data when a firm faces a general nonparametric demand function under imperfect competition. Under standard assumptions, we provide the constructive nonparametric identification of various firm-level objects: gross production function, total factor productivity, price markups over marginal costs, output prices, output quantities, a demand system, and a representative consumer’s utility function.
10419/229485
Keywords: Graue Literatur; nonparametric identification; production function; markup; total factor productivity; revenue